The system of equations tells you that y is equal to −2, so that’s the y-value in our system. To find the value of x in our system, we can substitute −2 for y in the second equation. Do that now.

y=−2
x=−9y+11
x
=
−9(
) + 11

1 answer

To find the value of \( x \) in the equation \( x = -9y + 11 \) when \( y = -2 \), substitute \( -2 \) for \( y \):

\[ x = -9(-2) + 11 \]

Now, multiply \(-9\) by \(-2\):

\[ x = 18 + 11 \]

Then, add \( 18 \) and \( 11 \):

\[ x = 29 \]

So, the value of \( x \) is \( 29 \).